Two-gap superconductivity in Ag1–xMo6S8 Chevrel phase. (17th November 2017) - Feig, Manuel; Bobnar, Matej; Veremchuk, Igor; Hennig, Christoph; Burkhardt, Ulrich; Starke, Ronald; Kundys, Bohdan; Leithe-Jasper, Andreas; Gumeniuk, Roman
Abstract: The superconducting properties of A g 1 − x Mo6 S8 [ x = 0.08 ( 1 ) ] Chevrel phase [ T c = 7.9 ( 5 ) K] are studied on a sample compacted by spark plasma sintering. Both lower ( B c 1 = 12 ( 1 ) mT) and the upper [ B c 2 ( 0 ) ≈ 7.4 ( 9 ) T] critical magnetic fields are obtained from magnetization and electrical resistivity measurements for the first time. The analysis of the low-temperature electronic specific heat indicates A g 1 − x Mo6 S8 to be a two band superconductor with the energy gaps Δ 1 = 1.6 meV (95%) and Δ 2 = 0.7 meV (5%). Theoretical DFT calculations reveal a much stronger electron–phonon coupling in the studied Chevrel phase compared to earlier reports. Similar to MgB2, the Fermi surface of studied Chevrel phase is formed by two hole-like and one electron-like bands.